The Comprehensive Investigation and Discussion on the Progress of Ethereum Proof-of-Stake - Feng Xiaojie (ITM Web of Conferences)
Proof of Stake (PoS), as an important consensus algorithm in blockchain technology, has received widespread attention and research in recent years. PoS aims to solve the problems of high energy consumption and low efficiency in Proof of Work (PoW) algorithms. By allowing validators to participate in the consensus process based on their economic interests, it achieves low energy consumption and high efficiency in block verification. This article examines the latest developments in five consensus algorithms for proof of stake, with the aim of identifying errors, omissions, and shortcomings in the original proof of stake. This article finds that although proof of stake has been widely used in the market, PoS algorithm still faces challenges such as how to further improve consensus efficiency, enhance system security, and effectively respond to malicious attacks. In order to address these challenges, this article presents some of its own opinions and proposes some summarized solutions and areas for improvement. This article aims to promote the continuous development of PoS algorithm through these perspectives, in order to adapt to more complex and diverse blockchain application scenarios.